Scientific Advancement and the Legacy of Islamic Civilization in Andalusian Historiography - Holilur Rahman; Lutfiah Syahnur (UIN Imam Bonjol Padang, 2025)
This article aims to examine the scientific advancements and legacy of Islamic civilization in Spain (Al-Andalus) as represented in Islamic historical literature, as well as to analyze the position of Andalusia within the historiography of global science. The central research problem explores how the concept of science in the Islamic tradition developed in Al-Andalus, the forms of scientific progress that emerged, and the ways in which both classical and modern historical sources construct narratives about Islamic Spain. This study employs a literature review design, analyzing Islamic history books, internationally indexed journal articles, and the works of classical Muslim historians alongside modern scholars. Data were collected through thematic literature exploration and evaluated using content analysis and historical synthesis. The findings reveal that Al-Andalus functioned as a major center of scientific civilization, contributing significantly to medicine, mathematics, astronomy, philosophy, and applied technologies, supported by an epistemological framework that integrated religion, reason, and knowledge. Furthermore, modern historiography indicates a paradigm shift away from Eurocentric narratives toward a more balanced recognition of Islamic scientific contributions. This article concludes that the legacy of Islamic civilization in Spain not only played a crucial role in shaping medieval European intellectual development but also provides a valuable model for contemporary studies of Islamic history and science, despite limitations related to a reliance on secondary sources and translated manuscripts that warrant further research.